Patterns of phenylpropanoids in non-inoculated and potato virus Y-inoculated leaves of transgenic tobacco plants expressing yeast-derived invertase - Sonnewald, Uwe; et al. (Phytochemistry, 2001)
The patterns of secondary metabolites in leaves of yeast invertase-transgenic tobacco plants (Nicotiana tabacum L. cv. Samsun NN) were analyzed. Plants expressing cytosolic yeast-derived invertase (cytInv) or apoplastic (cell wall associated) yeast invertase (cwInv) showed a characteristic phytochemical phenotype compared to untransformed controls (wild-type plants). The level of phenylpropanoids decreased in the cytInv plants but increased in the cwInv plants, which showed an induced de novo synthesis of a caffeic acid amide, i.e. N-caffeoylputrescine. In addition, the level of the coumarin glucoside scopolin was markedly enhanced. Increased accumulation of scopolin in the cwInv plants is possibly correlated with the induction of defense reactions and the appearance of necrotic lesions similar to the hypersensitive response caused by avirulent pathogens. This is consistent with results from potato virus Y-infected plants. Whereas there was no additional increase in the coumarins in leaves following infection in cwInv plants, wild-type plants showed a slight increase and cytInc a marked increase. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: Nicotiana tabacum; biotechnology; sugar sensing; yeast invertase; potato virus Y (PVY); phenylpropanoids; caffeic acid conjugates; scopolin